2019
DOI: 10.2298/ciceq180814009r
|View full text |Cite
|
Sign up to set email alerts
|

Technological and microbiological factors affecting the polyphenolic profile of Montenegrin red wines

Abstract: Article Highlights • The highest total content of phenolic compounds after AF and MLF was determined in Vranac wines • In Kratošija wines, phenolic compounds increased using BDX yeast and commercial LAB • Total phenolic compounds slightly decreased in Vranac wines inoculated with BDX and BM4x4 yeast • In Cabernet Sauvignon wines phenolic compounds decreased in ICVD21 wine inoculated with alpha LAB • Increase of stilbenes concentration was observed in all wines inoculated with commercial yeast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These compounds depend on variety; the influence of the vintage is not negligible, as well as the used winemaking technology. However, the content of caffeic acid was found to be the most abundant [70,71,119]. These data are not in accordance with results obtained by Lima et al [72], in whose study the predominant acid was p-coumaric (2.30-6.70 mg/L), followed by caffeic acid (0.52-1.49 mg/L), while the content of ferulic acid was up to 0.16 mg/L, in wines from the most used grape varieties in Portugal.…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 96%
See 2 more Smart Citations
“…These compounds depend on variety; the influence of the vintage is not negligible, as well as the used winemaking technology. However, the content of caffeic acid was found to be the most abundant [70,71,119]. These data are not in accordance with results obtained by Lima et al [72], in whose study the predominant acid was p-coumaric (2.30-6.70 mg/L), followed by caffeic acid (0.52-1.49 mg/L), while the content of ferulic acid was up to 0.16 mg/L, in wines from the most used grape varieties in Portugal.…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 96%
“…Their results indicated that the use of native yeast can considerably affect the composition of polyphenolic compounds. The significant influence of different commercial yeasts on the concentration of total, and some individual, phenolic compounds resulted in an increased of total phenolic compounds, and particularly stilbenes [70]. Besides the use of yeast, i.e., performing the traditional fermentation or using commercial selected dry yeast or isolated native yeast, it is also possible to vary other parameters.…”
Section: Changes During Alcoholic Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the phenolic composition of some varieties of grapes and wines, produced in different years and in several locations, were conducted in Montenegro (Minić, 2021). The influence of some seasonal variations in temperature and rainfall is reflected in the content of total polyphenols in red variety wines (Pajović et al, 2014;Šućur et al, 2016;Raičević et al, 2017;Radonjić et al, 2019). The presence of some individual phenolic compounds in wines reflects its varietal specificity, and shows little difference in relation to the wine region where the vines were grown (Pajović-Šćepanović et al, 2018).…”
Section: Introductionmentioning
confidence: 99%